A Comparison between the Instantaneous Wave-free Ratio and Resting Distal Coronary Artery Pressure/Aortic Pressure and the Fractional Flow Reserve: The Diagnostic Accuracy Can Be Improved by the Use of both Indices - Shiode, Nobuo (Intern Med, 2017)
OBJECTIVES: The fractional flow reserve (FFR) is an index of the severity of coronary stenosis that has been clinically validated in several studies. The instantaneous wave-free ratio (iFR) and the resting distal coronary artery pressure/aortic pressure (Pd/Pa) are nonhyperemic pressure-derived indices of the severity of stenosis. This study sought to examine the diagnostic accuracy of the iFR and resting Pd/Pa with respect to hyperemic FFR. METHODS: Following an intracoronary injection of papaverine, the iFR, resting Pd/Pa, and FFR were continuously measured in 123 lesions in 103 patients with stable coronary disease. RESULTS: The iFR and resting Pd/Pa values were strongly correlated with the FFR (R=0.794, p<0.001, R=0.832, p<0.0001, respectively). A receiver operator curve (ROC) analysis revealed that the optimal iFR cut-off value for predicting an FFR of <0.80 was 0.89 (AUC 0.901, sensitivity 84.1%, specificity 80.0%, positive predictive value 69.8%, negative predictive value 90.0%, diagnostic accuracy 81.3%), while the optimal resting Pd/Pa cut-off value was 0.92 (AUC 0.925, sensitivity 90.9%, specificity 78.5%, positive predictive value 70.2%, negative predictive value 93.9%, diagnostic accuracy 82.9%). The lesions with an iFR value of ≤0.89 and a Pd/Pa value of ≤0.92 were defined as double-positive lesions, while the lesions with an iFR value of >0.89 and a Pd/Pa value of >0.92 were defined as double-negative lesions. In these 109 lesions, the sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were 92.3%, 82.9%, 75.0%, 95.1%, and 86.2%, respectively. CONCLUSION: This analysis demonstrated that the iFR and resting Pd/Pa were strongly correlated with the FFR and that the diagnostic accuracy of the iFR was similar to that of the resting Pd/Pa. The diagnostic accuracy can be improved with the use of both the iFR and the resting Pd/Pa.